Diagnosis of copy number variants using array-based comparative genomic hybridisation in fetuses and neonates with congenital abnormalities in a South African population - Greeff, Reine Athena (Stellenbosch : Stellenbosch University, 2023)
Greeff, Reine Athena. 2023. Effect of biological oxidants on the functioning of MEP pathway’s [Fe-S] cluster-dependent enzymes. Unpublished masters dissertation. Stellenbosch : Stellenbosch University [online]. Available at: https://scholar.sun.ac.za/items/a958dab7-9a72-4217-81a3-e15ce18081fa